Theoretical Insights and Solvatochromic Behavior of 1,3-Benzodioxole Derivatives - Prasad, K. N. N.; Chandrasekhar, S. (Current Research Progress in Physical Science Vol. 3, 2024)
The use of spectroscopic techniques, including UV–vis absorption and fluorescence, combined with quantum chemical calculations, allowed us to gain a comprehensive understanding of the (E)-1-(4-hydroxypiperidin-1-yl)-3-(7-methoxybenzo[d][1,3] dioxol-5-yl)prop-2-en-1-one compounds' photophysical properties. The various solute and solvent interactions were investigated using Catalan's and Kamlet's techniques. The compound's excited state dipole moment was estimated using Lippert, Kawski-Chamma-Viallet, Bakhshiev, and \(E_N^T\) solvent polarity parameters. It had been found that the excited state dipole moment was greater than the dipole moment in the ground state. Variations in the solvent's polarity have a direct impact on the distribution of energy in ES. AS and NAS showed a surge in Stokes' shift, which rises with increasing solvent polarity. There could be specific solute-solvent interactions causing this. The redshift results from an effective intermolecular interface with the ES of the polar solvents caused by a significant distinction between the solute's ES and the spreading of GS charge. Further study was conducted to understand further the compound's molecular properties using computational approaches.